Fluorapatite solubilization by Aspergillus niger in vinasse medium - Nahas, E. [UNESP]; Banzatto, D. A. [UNESP]; Assis, L. C. [UNESP] (Elsevier, 1990)
Fluorapatite solubilization by Aspergillus niger using diluted vinasse at a relative density of 45° Brix may be an alternative to the usual processes for obtaining soluble phosphate. After 13 days of culture, a production of 1.2g l-1 soluble phosphate was obtained for 5g l-1 fluorapatite added to the vinasse, as well as production of 11 gl-1 dry mycelial mass and a substantial reduction of the polluting components of the medium, i.e. a 78 and 94% reduction of total and reducing sugars, respectively, and a 48 and 80% reduction of total and soluble solids, respectively. In less diluted medium, increased sugar content led to a greater production of dry mass but also to a reduction of soluble phosphate content. When fluorapatite concentration in vinasse was increased from 5.0 to 7.5 or 10.0 g l-1, soluble phosphate accumulation increased by 0.28 and 0.15 g l-1, respectively. Addition of ammonium nitrate or rotary shaking of the culture mixture did not lead to the production of larger amounts of soluble phosphate than obtained in the absence of these factors. © 1990.